Edukasi Hukum Undang-Undang Tentang Konservasi Sumber Daya Alam Hayati di UMKM EduWisata “Ndalem Kerto” Njenangan Ponorogo Guna Mewujudkan Wisata Alam Fauna Yang Ramah Di Kalangan Anak Usia Dini. - Muhammad 'Azam Muttaqin; Azis Akbar Ramadhan; Fifi Arisanti (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service program involves a series of interactive outreach to the owners of the Eduwisata "Ndalem Kerto" MSME Njenangan Ponorogo and tourist visitors, mostly children in the age group, which includes material about biological natural resources, animal management, tourist park management, legal protection for animals, as well as complaint mechanisms. Legal education is provided to help especially "Ndalem Kerto" MSME owners in dealing with cases related to animal management, most of which are protected animals such as peacocks and starlings which are entertainment, especially for young children. Through an inclusive and community-based approach, it is hoped that "Ndalem Kerto" MSME owners and visitors will be more empowered, educated and able to advocate for their rights effectively. The implementation method is carried out through the stages of searching for cases of public complaints, determining cases, planning, implementation, evaluation and follow-up. The results of this education show a significant increase in the legal knowledge of participants including "Ndalem Kerto" MSME owners and visitors in accessing and utilizing legal services. Thus, this program not only contributes to individual empowerment, but also strengthens society as a whole in efforts to enforce law and social justice.